Does Financial Globalization Induce Better Macroeconomic Policies? - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2004)
Monetary and fiscal policies around the world are in better shape today than two decades ago. This paper studies whether financial globalization has helped induce governments to pursue better macroeconomic policies (the "discipline effect"). The empirical tests have two innovations. First, we recognize potential endogeneity of the observed capital flows in a given country and employ an instrumental variable approach that relies on the autonomous (global) component of the capital flows. Second, we recognize inherent discreteness in defining good versus bad macroeconomic policies and use a transition matrix technique to determine whether capital flows are effective in inducing substantial qualitative policy shifts. Our results suggest that, in spite of the plausibility of the "discipline effect" in theory, it is not easy to find strong and robust causal evidence. There is some evidence that financial globalization may have induced countries to pursue low-inflation monetary policies. However, there is no evidence that it has encouraged low budget deficits.